Serum Levels of Cytokines in Subjects With Generalized Chronic and Aggressive Periodontitis Before and After Non‐Surgical Periodontal Therapy: A Pilot Study - Duarte, Poliana Mendes; da Rocha, Marcelo; Sampaio, Eduardo; Mestnik, Maria Josefa; Feres, Magda; Figueiredo, Luciene Cristina; Bastos, Marta Ferreira; Faveri, Marcelo (Journal of periodontology (1970), 2010)
Background: The emergence of periodontal medicine has increased interest in defining the serologic profiles of inflammatory mediators in subjects with periodontitis. Thus, the aim of this pilot study is to evaluate the serum levels of tumor necrosis factor‐alpha (TNF‐α), interferon‐γ, and interleukin (IL)‐4, ‐17, and ‐23 in subjects with generalized chronic periodontitis (GCP) and generalized aggressive periodontitis (GAgP) before and after non‐surgical periodontal therapy. Methods: Cytokines were measured by enzyme‐linked immunosorbent assay in serum samples taken from 42 systemically healthy subjects divided according to periodontal status into subjects with GAgP (n = 14) and GCP (n = 14) and periodontally healthy (PH) subjects (n = 14). In addition, the levels of cytokines were reassessed at 6 months after periodontal therapy in the periodontitis groups. Clinical parameters were also evaluated at baseline and 6 months post‐therapy. Results: After therapy, both periodontitis groups demonstrated a significant improvement in clinical periodontal status (P <0.05). At baseline, concentrations of TNF‐α (P = 0.0006) and IL‐17 (P = 0.02) were significantly higher in the GAgP group compared to the other groups. There was a significant decrease in serum concentrations of TNF‐α (P = 0.03) and IL‐17 (P = 0.04) at 6 months post‐therapy in the GAgP group (P <0.05). The concentration of TNF‐α remained elevated in the GAgP group compared to the PH group at 6 months post‐therapy (P = 0.04). Conclusions: Subjects with GAgP presented higher levels of TNF‐α and IL‐17 than subjects with GCP and PH subjects. In addition, although the serum levels of these cytokines improved significantly as a result of periodontal therapy, the levels of TNF‐α remained higher in subjects with GAgP compared to PH subjects.